Management strategies for acutely decompensated aortic stenosis. (14th October 2021) - Orzalkiewicz, M; Donati, F; Santona, L; Marcelli, C; Chietera, F; Bendandi, F; Bruno, A G; Ghetti, G; Taglieri, N; Palmerini, T; Marrozzini, C; Galie, N; et al.
Abstract: Background: Uncertainty exists over the optimal treatment strategy for patients presenting with acutely decompensated severe aortic stenosis (AS). The available options include a bridging balloon aortic valvuloplasty (BAV) or a direct transcatheter aortic valve implantation (TAVI). Purpose: Our study compares TAVI outcomes in patients treated with two different strategies in acutely decompensated severe AS: bridged TAVI vs direct TAVI. Methods: In this observational study all patients admitted with decompensated severe AS who underwent balloon aortic balloon valvuloplasty (BAV) and/or TAVI on the index admission were included. Comparison was made between bridged TAVI group (defined as initial BAV followed by TAVI) and direct TAVI group (TAVI on the index admission without bridging BAV). For this analysis we excluded patients in cardiogenic shock. Baseline characteristics, echocardiographic and periprocedural data were recorded in hospital database. Major adverse cardiovascular events (MACE) were defined as death, major bleeding, rehospitalisation for heart failure, or stroke). The follow-up data was obtained by outpatient visits and/or telephone calls. Results: 178 patients with acutely decompensated AS were analysed: 58 bridged TAVI, 23 direct TAVI, 9 bridged SAVR and 88 destination BAV (defined as BAV non followed by a definite treatment). There was no statistically significant difference between bridged TAVI and direct TAVI group in mean age (83.6±6.6 vs 80.4±8.3 years), the prevalence major comorbidities (coronary, respiratory, neurological or peripheral vascular disease), renal function (eGFR 43.4±18.9 vs 45.2±20.9 ml/min/m 2 ), the mean LV ejection fraction (53.4±13.8 vs 48.6±14.6%) or aortic valve gradient (39.4±13.0 vs 34.1±12.3mmHg), respectively. Direct TAVI patients had a higher mean surgical risk scores (STS 6.1±3.7 vs 9.1±7.0%, logES 18.8±11.5 vs 30.8±20.9%, p=0.01) and higher prevalence of significant aortic regurgitation (5% vs 43%, p=0.0001). The femoral TAVI access was used in 98% of bridged and 78% of direct TAVI patients (p=0.006). The estimated 1-year survival and 1-year MACE-free survival did not differ significantly between the bridged TAVI and direct TAVI groups (86.8% vs 78.3%, p=0.20 and 79.7% vs 64.2%, p=0.11, respectively). Conclusions: A large proportion of patients admitted with acutely decompensated AS were not eligible for definite treatment. There is no difference in procedural success, 1-year all-cause mortality and 1-year major adverse cardiovascular events between the bridged TAVI or direct TAVI strategies in acute decompensated aortic stenosis allowing to personalize treatment strategy for individual patient. Funding Acknowledgement: Type of funding sources: None.